2012
DOI: 10.1111/j.1939-1676.2012.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Esomeprazole and Cisapride on Gastroesophageal Reflux During Anesthesia in Dogs

Abstract: Background: Gastroesophageal reflux (GER) is common in anesthetized dogs and can cause esophagitis, esophageal stricture, and aspiration pneumonia.Objective: To determine whether preanesthetic IV administration of esomeprazole alone or esomeprazole and cisapride increases esophageal pH and decreases the frequency of GER in anesthetized dogs using combined multichannel impedance and pH monitoring.Animals: Sixty-one healthy dogs undergoing elective orthopedic surgery procedures. Methods: Prospective, randomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 39 publications
3
65
1
4
Order By: Relevance
“…However, PK information relating to the use of esomeprazole in veterinary medicine is not available, and little published support exists regarding esomeprazole dosages in dogs 17. IV administration of esomeprazole (1 mg/kg) and cisapride (1 mg/kg) 12–19 hours and 1–1.5 hours before anesthesia resulted in decreased gastroesophageal reflux 7. However, this evidence is insufficient to support a dosage regimen for oral and parenteral esomeprazole administration in dogs 17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PK information relating to the use of esomeprazole in veterinary medicine is not available, and little published support exists regarding esomeprazole dosages in dogs 17. IV administration of esomeprazole (1 mg/kg) and cisapride (1 mg/kg) 12–19 hours and 1–1.5 hours before anesthesia resulted in decreased gastroesophageal reflux 7. However, this evidence is insufficient to support a dosage regimen for oral and parenteral esomeprazole administration in dogs 17.…”
Section: Discussionmentioning
confidence: 99%
“…In 8‐week clinical trials involving patients with erosive esophagitis, the treatment group receiving esomeprazole showed significantly higher healing rates than patients receiving omeprazole or lansoprazole 4. In veterinary medicine, however, little information has been published about the PKs and acid suppressant efficacy of esomeprazole in dogs 7, 8…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2004) reported that oral administration of omeprazole every 12 h for 7 days did not decrease GER. Esomeprazole is the proton pump inhibitor studied in dogs; dogs that received IV esomeprazole (1 mg/kg) alone in a prospective randomized placebo-controlled study presented significant increase in gastric and esophageal pH, but the drug did not significantly decrease GER frequency; however, combination of esomeprazole (1 mg/kg) and cisapride (1 mg/kg) IV was associated with significant decrease of reflux in anaesthetized dogs (Zacuto et al ., 2012). Ranitidine has been used in dogs to reduce GER during anesthesia, but results vary.…”
Section: Preventing Ger During Anesthesiamentioning
confidence: 99%
“…A single dose of omeprazole, given four hours before the induction of anaesthesia reduces the occurrence of reflux (Panti and others 2009). However, another study found no improvement in reflux when esomeprazole was given alone (Zacuto and others 2012). Tolbert and others (2015) theorised that because PPIs require several days to reach full effect, the addition of a dose of ranitidine would reduce GER.…”
Section: Prevention and Treatmentmentioning
confidence: 99%